2020
DOI: 10.1021/acs.macromol.0c00533
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular Chiral Amplification through a Random Coil to One-Handed Helix Transformation Induced by Metal Ion Coordination in an Aqueous Solution

Abstract: Many inspiring achievements have been made in inducing chiral amplification in helical polymers; however, the induction of helical chirality in random coil polymers by the intermolecular noncovalent force in solutions so far is still an intractable task, which is almost only accomplishable in biopolymer systems. In this contribution, we found that a random coil poly(Npropargylamide) with an L-or D-alanine residue as the pendant (P-L(or -D)-ala-NH 2 ) can be induced to form a predominantly onehanded helical str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 98 publications
1
9
0
Order By: Relevance
“…However, the addition of 25% of the isomer considerably changed the specific rotation of poly-( l 0.75 - co - d 0.25 )-ala-Boc or poly-( l 0.25 - co - d 0.75 )-ala-Boc. As reported in our previous study, poly- l -ala-Boc and poly- d -ala-Boc realized a helical conformation in the CHCl 3 solution . Interestingly, poly-( l 0.9 - co - d 0.1 )-ala-Boc and poly-( l 0.1 - co - d 0.9 )-ala-Boc exhibited almost the same CD spectral patterns as homopolymers (Figure b), indicating that the one-handed helical structure of poly-( l 0.9 - co - d 0.1 )-ala-Boc or poly-( l 0.1 - co - d 0.9 )-ala-Boc hardly changes.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…However, the addition of 25% of the isomer considerably changed the specific rotation of poly-( l 0.75 - co - d 0.25 )-ala-Boc or poly-( l 0.25 - co - d 0.75 )-ala-Boc. As reported in our previous study, poly- l -ala-Boc and poly- d -ala-Boc realized a helical conformation in the CHCl 3 solution . Interestingly, poly-( l 0.9 - co - d 0.1 )-ala-Boc and poly-( l 0.1 - co - d 0.9 )-ala-Boc exhibited almost the same CD spectral patterns as homopolymers (Figure b), indicating that the one-handed helical structure of poly-( l 0.9 - co - d 0.1 )-ala-Boc or poly-( l 0.1 - co - d 0.9 )-ala-Boc hardly changes.…”
Section: Resultssupporting
confidence: 77%
“…In previous studies, 50 the P-L(or-D)-ala-NH 2 /Cu 2+ complex in the NIR region (450−850 nm) exhibited clear CD (Figure 4b), which belonged to different orbital d−d* transitions due to the d orbital energy level splitting of Cu 2+ , 58 where a nearly square structure was formed by coordinating Cu 2+ with four nitrogen atoms of two amino-acid amides (Figure 3d). This result further demonstrated that a special interaction between the poly-(L-co-D)-ala-NH 2 and Cu 2+ was metal coordination.…”
Section: Synthesis Ofmentioning
confidence: 81%
“…Chiral assemblies with controllable ICDs open up new perspectives in the field of chiroptical applications, including but not limited to optical amplifier materials, 23,36,37 chiral sensing, 38,39 optical switch, and data storage applications. [40][41][42] Furthermore, a research group in Spain has shown that the supramolecular gels can be applied as organic reaction media.…”
Section: Discussionmentioning
confidence: 99%
“…However, most notably, the conformation adjustment of subunit structures can feasibly induce helical inversion. Tunable helical senses of polymers by changing the polarity, donor character, solvation ability of the solvent, or complexation with metal ions have been described. For example, Yashima et al reported that the screw senses of polyphenylacetylene (PPA) bearing achiral phosphonic acid monoesters as the pendant groups were inverted by the adjustment of the asymmetrical position in phosphorus pendants or chiral amine additives in different solvents . Riguera and Freire et al demonstrated that the sp/ap equilibrium in (O)­C–C­(−O) at the pendants was shifted to change the helical senses by complexation with different metal ions. Interestingly, their work involves the cis-trans isomerization of secondary amides induced by changing the donor character of solvents, which would modulate both the elongation and rotation of PPA .…”
Section: Introductionmentioning
confidence: 99%